Identification of Sphingomonads on the Basis of Polymerase Chain Reaction Amplified 16S rRNA Gene - Tokajian, Sima (2008)
Sphingomonas is a genus that is basically of environmental origin but can also be associated with health hazards, especially in the hospital environment where there is a great need to properly monitor water sources. The abundance and frequent isolation of derivatives of yellow pigmented colonies from drinking water samples in Lebanon — where an intermittent mode of supply is employed, and which induces frequent biofilm sloughing — necessitated the establishment of a rapid and feasible assay to screen specifically for sphingomonads. In this study, 50 isolates recovered from drinking water with yellow- to orange-pigmented colonies were used to establish a polymerase chain reaction-based (PCR-based) screening assay. The use of sphingomonad specific modified primers gave one common band with a size of 320 bp in all presumptive and sequence confirmed sphingomonads. However, no amplification was observed with Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Applying the PCR-based assay described in this paper increased both the efficiency and the reliability of screening for sphingomonads in water samples, thereby minimizing related risk factors.